2021
DOI: 10.3390/w13223273
|View full text |Cite
|
Sign up to set email alerts
|

Changing Causes of Drought in the Urmia Lake Basin—Increasing Influence of Evaporation and Disappearing Snow Cover

Abstract: The water level of the Urmia Lake Basin (ULB), located in the northwest of Iran, started to decline dramatically about two decades ago. As a result, the area has become the focus of increasing scientific research. In order to improve understanding of the connections between declining lake level and changing local drought conditions, three common drought indices are employed to analyze the period 1981–2018: The Standard Precipitation Index (SPI), the Standard Precipitation-Evaporation Index (SPEI), and the Stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Previous studies compared the accuracy of ERA5 to observed data from several basins in Iran, indicating that ERA5 can be used as a potential source of weather data in basins with low densities of meteorological stations [82,83]. We also recommend using ERA5 as a source of weather data in the Urmia Lake Basin, which is consistent with the findings of M. Habibi et al [84].…”
Section: Comparison Of Era5 and Era-interim Precipitation And Tempera...supporting
confidence: 88%
“…Previous studies compared the accuracy of ERA5 to observed data from several basins in Iran, indicating that ERA5 can be used as a potential source of weather data in basins with low densities of meteorological stations [82,83]. We also recommend using ERA5 as a source of weather data in the Urmia Lake Basin, which is consistent with the findings of M. Habibi et al [84].…”
Section: Comparison Of Era5 and Era-interim Precipitation And Tempera...supporting
confidence: 88%
“…The study conducted by Safarianzengir et al 33 highlighted a strong correlation between the decline in groundwater and a decreasing trend in snowfall in Iran (2000–2019). Recent observations also reported a decline in snowfall in different parts of Iran during the last decades 34 36 .…”
Section: Resultsmentioning
confidence: 86%
“…Terrestrial open-surface water bodies, such as lakes, reservoirs, ponds, streams, and rivers, play a crucial role as water resources for agriculture, industrial production, and both aquatic and terrestrial ecosystems [1][2][3]. Climate change and human activities have significant effects on water resources, impacting both quantity and quality [4].…”
Section: Introductionmentioning
confidence: 99%